Identifying the Determinants of Dividend Payout Ratios in Nepalese Commercial Banks - Dhungana, Bharat Ram; Gautam, Sushma; Ranabhat, Deepesh; Ojha, Deepak; Lamichhane, Keshav; Acharya, Sujana (Journal of Business and Social Sciences Research, 2024)
The banking sector in Nepal has experienced significant growth since its formal inception, playing a crucial role in the country's economic development. This study aims to explore the factors influencing the dividend payout ratio in commercial banks of Nepal. The research is based on secondary data to analyse the commercial banks operating in Nepal. Quota sampling was employed to select seven banks, and data were analysed using descriptive and analytical research designs, along with statistical tools like regression analysis. The findings reveal that liquidity ratio and bank size have a significant positive impact on dividend payout ratios in Nepalese commercial banks. However, variables such as leverage, capital adequacy ratio, and profitability ratios exhibit insignificant relationships. Additionally, significant differences in dividend payout ratios, return on assets, leverage, and capital adequacy ratio were observed among different bank types. Higher liquidity ratios and larger bank sizes correspond to higher dividend payout ratios, indicating their pivotal role in shaping dividend policies in Nepalese commercial banks. Banks and financial institutions may focus on managing liquidity and expanding their size to enhance the dividend payout ratio.